EFFECTS OF DIFFERENT VOLUMES OF NITROGEN GAS FUMIGATION ON POSTHARVEST PERFORMANCES MINIMALLY PROCESSED PINEAPPLE (Ananas Comosus L.) - Mubarak A.; Tan G.I.; Wan Zaliha W.S (UNEJ e-Proceeding, 2017)
Fresh cut pineapple has a high popularity nowadays because of its fresh like quality, readyto-eatpropertiesandhighnutritionalvalue.However,priortopeelingandcuttingprocesses, fresh cut pineapple is usually susceptible to browning incidence, which was catalysed bypolyphenol oxidase (PPO) enzyme. Browning incidence generally degraded the overallattributes of fresh cut pineapple, and simultaneously, limited its shelf life. In present study,the effects of different volumes of nitrogen (N2) gas (0 mL, 5 mL, 10 mL, 15 mL, 20 mL and 25mL) on fresh cut pineapples were evaluated under 5 ºC storage for nine days. The parametersbeing evaluated were browning incidence, flesh colour, total phenolic content, ascorbic acidconcentration, flesh firmness, soluble solids concentration and titratable acidity. It is shownthat N2 gas fumigation at higher volume had significant effect (p≤0.05) in reducing browningincidence of fresh cut pineapple. However, no apparent effects were found in otherpostharvest parameters. In conclusion, fumigation with 25 mL of N2 gas has a tendency indelaying the occurrence of browning, and maintaining other quality attributes of fresh cutpineapple.